Sinks in Healthcare Facilities Are a Potential Source for Dissemination of Candida Species. (4th October 2017) - Jencson, Annette; Cadnum, Jennifer; Piedrahita, Christina; John, Amrita; Alhmidi, Heba; Jacobs, Michael; Donskey, Curtis
Abstract: Background: Healthcare facility sinks have been implicated in transmission of bacterial pathogens, including multidrug-resistant Gram-negative bacilli. However, it is not known if sinks might also be an important source for dissemination of Candida species. Methods: In 4 Cleveland area hospitals, we determined the frequency of dissemination of Candida species from sink drains to the sink bowl and countertop. The sink drain, bowl, and adjacent countertop were cultured; the sink bowl and countertop were then disinfected and additional cultures were collected from the sink bowl and countertop after running the water for 30 seconds. Candida species recovered were identified using MALDI-TOF. Results: A total of 194 sets of cultures were collected from the 4 hospitals (range, 40 to 74 cultures per hospital). As shown in the figure, Candida species were frequently recovered from the sink bowls and countertops at baseline and dissemination to these sites occurred frequently when the water was run. Candida parapsilosis was the most frequent Candida species recovered, followed by Candida tropicalis and Candida lusitaneae . Conclusion: Our findings suggest that sinks may be an under-appreciated reservoir for dissemination of Candida species in hospitals. Disclosures: All authors: No reported disclosures.